Regression of left ventricular hypertrophy and prevention of left ventricular dysfunction by captopril in the spontaneously hypertensive rat. - Pfeffer, J M (1982)
To determine whether chronic antihypertensive therapy prevents the progression of cardiac hypertrophy and the deterioration in cardiac performance observed in spontaneously hypertensive rats (SHR) with long-term hypertension, 14-month-old female SHR and normotensive American Wistar rats (NWR) were treated for 10 months with an inhibitor of angiotensin I-converting enzyme, captopril (2 g/liter of drinking water). Captopril reduced the marked left ventricular hypertrophy of 24-month-old SHR (untreated, 4.37 +/- 0.2 mg/g of body weight; treated, 3.01 +/- 0.1 mg/g; P less than 0.02) to levels observed in 6-month-old SHR. Treatment prevented the reductions in baseline and maximal aortic blood flows that occurred in SHR between ages 12 and 24 months yet had no effect on the blood flows of NWR. The diminished maximal stroke volume of untreated SHR was ejected from a significantly increased left ventricular end-diastolic volume, so that the ejection-fraction index was markedly reduced (24-month-old untreated NWR, 84 +/- 3%; untreated SHR, 56 +/- 5%; P less than 0.001). Therapy restores this index in SHR to normal (77 +/- 4%). The relationship between ejection-fraction index, and afterload was also normal in treated SHR. Thus, chronic therapy with captopril produced a marked regression of cardiac hypertrophy and prevented the deterioration of cardiac performance in SHR with long-standing hypertension.